Nitrogen-doped phenolic acid-based carbon dots with surface modified silane chains, and preparation method and application thereof

CN122998381APending Publication Date: 2026-10-30CHINA AGRI UNIV SANYA RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611514349.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]针对现有技术的不足,本发明的目的在于提供一种表面修饰有硅烷链的氮掺杂酚酸基碳点及制备方法和应用,以解决上述现有酚酸基碳点所存在的技术问题

Benefits of technology

(1)本发明制备的碳点通过调控氮源与有机硅季铵盐之间的添加比例,能够实现对革兰氏阳性菌和革兰氏阴性菌的选择性杀伤。实验表明,在不同比例下,该碳点对耐甲氧西林金黄色葡萄球菌和铜绿假单胞菌的杀菌率均可达99%以上,显示出优异的广谱抗菌性能以及协同抗菌效果;同时,通过调整硅烷链与氮源的比例,可定向增强对特定菌种的杀伤效果,突破了传统抗菌剂无差别杀菌的应用局限。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998381A_ABST
    Figure CN122998381A_ABST
Patent Text Reader

Abstract

The application discloses nitrogen-doped phenolic acid-based carbon dots which are surface-modified with silane chains, and the carbon dots are composed of a carbon core and an organic silicon quaternary ammonium salt modified on the surface of the carbon core, the carbon core is a carbon skeleton formed by hydrothermal carbonization with a phenolic compound as a carbon source, and the carbon skeleton is doped with nitrogen elements. The carbon dots prepared by the application can selectively kill gram-positive bacteria and gram-negative bacteria by regulating the adding proportion between a nitrogen source and the organic silicon quaternary ammonium salt. Experiments show that the bactericidal rates of the carbon dots on methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa can reach more than 99% under different proportions, and the carbon dots show excellent broad-spectrum antibacterial performance and synergistic antibacterial effect. Meanwhile, by adjusting the proportion of the silane chains and the nitrogen source, the killing effect on specific bacteria can be directionally enhanced, and the application limitation of traditional antibacterial agents without differential sterilization is broken through.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of antibacterial drug preparation technology, and specifically to a nitrogen-doped phenolic acid carbon dot with a surface modified with silane chains, its preparation method, and its application. Background Technology

[0002] The overuse of antibiotics has led to the widespread transmission of drug-resistant pathogens (such as methicillin-resistant Staphylococcus aureus), causing traditional antibiotics to become less effective or even ineffective in treating bacterial infections. Therefore, developing novel, highly effective, low-toxicity antimicrobial materials that are less likely to induce drug resistance is of great significance.

[0003] Phenolic acids (such as gallic acid and caffeic acid) are widely found naturally in various plants. Their molecular structure contains multiple phenolic hydroxyl groups, giving them certain antibacterial activity. They are often used as raw materials for the synthesis of pharmaceutical or food preservatives. However, the antibacterial effect of free phenolic acids is limited and cannot meet the needs of practical applications.

[0004] Carbon dots (CDs) are a class of zero-dimensional carbon nanomaterials with advantages such as small particle size (1~10 nm), ease of surface functionalization, and good biocompatibility, showing broad application prospects in the field of antibacterial applications. In recent years, some studies have attempted to convert natural phenolic acid compounds into carbon dots to enhance their antibacterial properties.

[0005] However, existing phenolic acid carbon dots mainly enhance their antibacterial effect by increasing their specific surface area to improve their interaction with bacteria. Their surface functional groups are singular, lacking active targeting or membrane disruption functions, resulting in limited improvement in antibacterial efficacy. More importantly, existing carbon dots lack selective killing ability against different types of bacteria (Gram-positive and Gram-negative bacteria), making it difficult to achieve precise antibacterial treatment. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a nitrogen-doped phenolic acid carbon dot with a surface modified with silane chains, a preparation method and application, so as to solve the technical problems existing in the above-mentioned existing phenolic acid carbon dots.

[0007] To achieve this objective, the present invention adopts the following technical solution: A first aspect of the present invention is to provide a nitrogen-doped phenolic acid-based carbon dot with a surface modified with a silane chain, the carbon dot being composed of a carbon core and an organosilicon quaternary ammonium salt modified on the surface of the carbon core, wherein the carbon core is a carbon skeleton formed by hydrothermal carbonization using phenolic acid compounds as a carbon source, and the carbon skeleton is doped with nitrogen.

[0008] In one optional embodiment, the phenolic acid compound is gallic acid, protocatechuic acid, tannic acid, caffeic acid, chlorogenic acid, or ferrochrome.

[0009] In one optional embodiment, the organosilicon quaternary ammonium salt is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride; and the nitrogen source is ethylenediamine.

[0010] A second aspect of the present invention is to provide a method for preparing nitrogen-doped phenolic acid carbon dots with surface-modified silane chains, comprising the following steps: (1) Dissolve phenolic acid compounds, organosilicon quaternary ammonium salts and nitrogen sources in a mixed solvent composed of ultrapure water and ethanol to obtain a precursor solution; (2) The precursor solution obtained in step (1) is placed in a reaction vessel for hydrothermal reaction; (3) After the reaction is complete, allow the mixture to cool naturally, centrifuge the product and take the supernatant. (4) The supernatant was placed in a dialysis bag for dialyzing, and after freeze-drying, nitrogen-doped phenolic acid carbon dots with silane chains on the surface were obtained.

[0011] In an optional embodiment, in step (1), the ratio of phenolic acid compound: organosilicon quaternary ammonium salt: nitrogen source = (1-2) g: (2-10) mL: 1 mL.

[0012] In one alternative embodiment, in step (1), the volume ratio of ultrapure water to ethanol in the mixed solvent is 60:40, and the amount used is 30 mL.

[0013] In an optional embodiment, in step (2), the reactor is heated to 160-220°C at a heating rate of 2-5°C / min and reacted for 12-18 h.

[0014] In one alternative embodiment, in step (3), the centrifugation speed is 8000-12000 r / min and the time is 10-15 min.

[0015] In an alternative embodiment, in step (4), the molecular weight cut-off of the dialysis bag is 1000-1200 Da.

[0016] A third aspect of the present invention is to provide the application of the nitrogen-doped phenolic acid carbon dots with surface-modified silane chains in the preparation of antibacterial drugs.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The carbon dots prepared in this invention can selectively kill Gram-positive and Gram-negative bacteria by adjusting the addition ratio between nitrogen source and organosilicon quaternary ammonium salt. Experiments show that, under different ratios, the carbon dots can achieve a bactericidal rate of over 99% against methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa, demonstrating excellent broad-spectrum antibacterial properties and synergistic antibacterial effects; at the same time, by adjusting the ratio of silane chain to nitrogen source, the killing effect on specific bacterial species can be enhanced in a targeted manner, breaking through the application limitations of traditional antibacterial agents that kill bacteria indiscriminately.

[0018] (2) The average particle size of the carbon dots in this invention is 5~8 nm, and the size distribution is uniform. The uniform ultra-small size is conducive to the nanomaterials penetrating the biological barrier or entering the host cell, thereby exerting a bactericidal effect efficiently.

[0019] (3) The carbon dots of the present invention maintain good biocompatibility with normal mammalian cells at high concentrations, with a cell survival rate of over 90%, and have good potential for clinical application safety.

[0020] (4) This invention uses gallic acid, a natural plant-derived phenolic acid compound, as the carbon source. The raw materials are widely available, inexpensive, and environmentally friendly. The one-step hydrothermal method is used to achieve in-situ carbon doping and surface silane chain modification. The operation is simple, no complicated purification steps are required, and it is suitable for large-scale production. Attached Figure Description

[0021] Figure 1 These are transmission electron microscope (TEM) images of the carbon dots obtained in Examples 1-3 of this invention.

[0022] Figure 2 The images show the UV-Vis absorption spectra of the carbon dots obtained in Examples 1-3 of this invention.

[0023] Figure 3 The images show the fluorescence absorption spectra of the carbon dots obtained in Examples 1-3 of this invention.

[0024] Figure 4 The image shows the minimum inhibitory concentration (MIC) of the carbon dots obtained in Examples 1-3 of this invention.

[0025] Figure 5 The carbon dots prepared in Examples 1-3 of this invention are shown to have bactericidal effects against methicillin-resistant Staphylococcus aureus USA300 and Pseudomonas aeruginosa PA01.

[0026] Figure 6 These are scanning electron microscope images showing the killing effect of carbon dots prepared in Examples 1-3 of this invention on the bacterial membranes of methicillin-resistant Staphylococcus aureus USA300 and Pseudomonas aeruginosa PA01.

[0027] Figure 7The results are the toxicity test results of the carbon dots obtained in Examples 1-3 of this invention. Detailed Implementation

[0028] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present application.

[0029] Example 1 This embodiment provides a nitrogen-doped phenolic acid carbon dot with a surface modified with silane chains, and its preparation method is as follows: Take 6 mL of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and ethylenediamine (the volume ratio of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to ethylenediamine is 2:1) and dissolve 2 g of gallic acid in 30 mL of solvent (60% ultrapure water + 40% ethanol) to obtain a precursor solution. Place the precursor solution in a polytetrafluoroethylene-lined reactor and heat it to 180 °C at a heating rate of 3 °C / min for 18 h. After allowing it to cool naturally overnight, remove it and centrifuge the product at 10,000 r / min for 12 min. Take the supernatant to remove large particles or insoluble impurities that are not fully carbonized. Then, place the supernatant in a dialysis bag with a molecular weight cutoff of 1000 Da for dialysis to completely remove unreacted free small molecules and solvent residues. Freeze-dry to obtain nitrogen-doped phenolic acid carbon dots with silane chains on the surface (silane chain: nitrogen = Si: N = 2:1).

[0030] Example 2 This embodiment provides a nitrogen-doped phenolic acid carbon dot with a surface modified with silane chains, and its preparation method is as follows: Take 6 mL of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and ethylenediamine (the volume ratio of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to ethylenediamine is 5:1) and dissolve 2 g of gallic acid in 30 mL of solvent (60% ultrapure water + 40% ethanol) to obtain a precursor solution. Place the precursor solution in a polytetrafluoroethylene-lined reactor and heat it to 220 °C at a heating rate of 5 °C / min for 12 h. After allowing it to cool naturally overnight, remove it and centrifuge the product at 12000 r / min for 10 min. Take the supernatant to remove large particles or insoluble impurities that are not fully carbonized. Then, place the supernatant in a dialysis bag with a molecular weight cutoff of 1000 Da for dialysis to completely remove unreacted free small molecules and solvent residues. Freeze-dry to obtain nitrogen-doped phenolic acid carbon dots with silane chains on the surface (silane chain: nitrogen = Si: N = 5:1).

[0031] Example 3 This embodiment provides a nitrogen-doped phenolic acid carbon dot with a surface modified with silane chains, and its preparation method is as follows: Take 6 mL of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and ethylenediamine (the volume ratio of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to ethylenediamine is 10:1) and dissolve 2 g of gallic acid in 30 mL of solvent (60% ultrapure water + 40% ethanol) to obtain a precursor solution. Place the precursor solution in a polytetrafluoroethylene-lined reactor and heat it to 200 °C at a heating rate of 5 °C / min for 16 h. After allowing it to cool naturally overnight, remove it and centrifuge the product at 8000 r / min for 15 min. Take the supernatant to remove large particles or insoluble impurities that are not fully carbonized. Then, place the supernatant in a dialysis bag with a molecular weight cutoff of 1000 Da for dialysis to completely remove unreacted free small molecules and solvent residues. Freeze-dry to obtain nitrogen-doped phenolic acid carbon dots with silane chains on the surface (silane chain: nitrogen = Si: N = 10: 1).

[0032] Comparative Example 1 The difference between this comparative example and Example 1 is that dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride is not added. The rest of the process is similar to that in Example 1, and single nitrogen-doped phenolic acid carbon dots are prepared.

[0033] Comparative Example 2 The difference between this comparative example and Example 1 is that ethylenediamine is not added, but the rest of the process is similar to that of Example 1, and phenolic acid carbon dots with silane chains on the surface are prepared.

[0034] Comparative Example 3 The difference between this comparative example and Example 1 is the volume ratio of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to ethylenediamine. In this comparative example, the volume ratio of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to ethylenediamine is 1:1. The rest of the process is similar to that in Example 1, and nitrogen-doped phenolic acid carbon dots with silane chains on their surface are prepared.

[0035] Comparative Example 4 The difference between this comparative example and Example 1 is the volume ratio of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to ethylenediamine. In this comparative example, the volume ratio of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to ethylenediamine is 15:1. The rest of the process is similar to that in Example 1, and nitrogen-doped phenolic acid carbon dots with silane chains on their surface are prepared.

[0036] Test Example 1 This test example characterizes the nitrogen-doped phenolic acid-based carbon dot materials with silane chains modified on the surface prepared in Examples 1-3.

[0037] The surface morphology of nitrogen-doped phenolic acid carbon dots (CDs) with silane chains modified on the surface was analyzed by transmission electron microscopy (TEM). The results are shown in [Figure number missing]. Figure 1 ,Depend on Figure 1 It can be seen that the particle size of CDs is 5~8 nm, and CDs have a distinct lattice structure with a lattice fringe spacing of 0.21~0.25 nm, which is similar to that of sp. 2 The (102) diffraction planes of graphite carbon are consistent, and its lattice structure gradually becomes more ordered as the proportion of silane chains increases.

[0038] This invention employs a specific ratio of alcohol to water co-solvent system (water to ethanol volume ratio of 3:2). This system not only perfectly overcomes the compatibility barrier between the hydrophilic carbon source (gallic acid) and the hydrophobic long-chain dopant (silane quaternary ammonium salt), but also provides a microenvironment with a suitable dielectric constant under high-temperature hydrothermal conditions. This allows nitrogen and long-chain alkanes to be more uniformly embedded or grafted onto the carbon dot surface, ultimately ensuring the formation of uniform particle sizes of 5–8 nm. By controlling the heating rate, the rapid and drastic carbonization of the carbon source can be effectively avoided, preventing the formation of large carbon polymer particles. This ensures that the product maintains an extremely small zero-dimensional size, which is crucial for nanomaterials to penetrate biological barriers or enter host cells to exert bactericidal effects.

[0039] The UV absorption peaks of nitrogen-doped phenolic acid-based carbon dot materials with surface-modified silane chains were analyzed using UV-Vis absorption spectroscopy. For example... Figure 2As shown, the UV-Vis absorption spectrum exhibits a broad absorption peak in the 400–600 nm range, which can be attributed to the π-π* transitions of CC or CO, indicating the presence of a carbon structure in the graphene core. Furthermore, the absorbance changes earlier when the ratio of silane chain to ethylenediamine is 5:1.

[0040] Fluorescence performance testing such as Figure 3 As shown, from Figure 3 As can be seen from the data, the fluorescence performance of CDs with different proportions is basically the same, with the optimal excitation wavelength being 336 nm and the optimal emission wavelength being 475 nm.

[0041] Test Example 2

[0042] I. Strain revival and subculturing Under aseptic conditions, methicillin-resistant Staphylococcus aureus (USA300) and Pseudomonas aeruginosa (PA01) were revived and inoculated into MHB medium, and cultured in a constant temperature shaking incubator at 37°C for 12 h. After passage and purification of the bacteria using the same inoculation method, they were ready for use.

[0043] II. Determination of Minimum Inhibitory Concentration (MIC) The minimum inhibitory concentration (MIC) against methicillin-resistant Staphylococcus aureus (USA300) and Pseudomonas aeruginosa (PA01) was determined using the micro-broth dilution method. The MIC concentrations of modified carbon dots with different Si:N ratios in wells 1 through 5 were 64, 32, 16, 8, and 4 μg / mL, respectively. After static incubation at 37 ℃ for 24 h, the MIC was determined by observing no microscopic growth in the well with the lowest carbon dot concentration. Results are as follows: Figure 4 As shown in the figure, the minimum inhibitory concentrations (MICs) of carbon dots against methicillin-resistant Staphylococcus aureus (USA300) and Pseudomonas aeruginosa (PA01) are 4 / 8 μg / mL and 16 μg / mL, respectively. The culture medium in wells with drug concentrations below the MIC became turbid, while bacterial growth was significantly inhibited at concentrations of 2 MIC and 4 MIC.

[0044] III. Bacterial sterilization rate Take the overnight culture and adjust the concentration OD. 600=0.5, washed three times with sterile PBS and resuspended (8000 r / min, 5 min). Pure gallic acid carbon dots, carbon dots from Examples 1-3, and Comparative Examples 1-4 were added to two different bacterial cultures and incubated for 12 h. After appropriate dilution, 100 μL was spread onto MHA solid medium and incubated at 37℃ for 24 h for colony counting. A bacterial control group was set up, and the experiment was performed in triplicate. The bactericidal activity of the carbon dots was evaluated using the plate count method. The bactericidal activity results of Examples 1-3 are shown below. Figure 5 As shown, carbon dots (CD) exhibit excellent broad-spectrum bactericidal activity. For the USA300 strain, the higher the proportion of alkyl chains, the better the antibacterial performance. At a ratio of 10:1, the bactericidal rate was 99.86±0.12%. For Gram-positive bacteria, silane chains can directly insert into the cell membrane to exert their effect, thus being more effective. However, for PA01 bacteria, plate count results showed that a ratio of 5:1 was more effective (bactericidal rate as high as 99.88±0.18%). It is speculated that improving the antibacterial performance against Gram-negative bacteria requires a more effective balance of long-chain alkanes and nitrogen source doping. The antibacterial results of all carbon dots are shown in Table 1.

[0045] Table 1. Antibacterial properties of carbon dots treated with different methods

[0046] The data in the table above show that the carbon dot materials prepared by the present invention (Examples 1-3) have certain inhibitory effects on methicillin-resistant Staphylococcus aureus (USA300) and Pseudomonas aeruginosa (PA01), exhibiting significant synergistic antibacterial and bactericidal effects, with inhibition rates all above 80%. Among them, the effect of nitrogen / silane chain dual modification is further superior to the other two single-functionalized carbon dot materials (Comparative Example 1 and Comparative Example 2). When the volume ratio of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to ethylenediamine is 5:1, the antibacterial effect against methicillin-resistant Staphylococcus aureus (USA300) reaches 93.57±0.17%, while the antibacterial effect against Pseudomonas aeruginosa (PA01) reaches 99.88±0.18%. When the volume ratio of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride to ethylenediamine is 10:1, the antibacterial effect against methicillin-resistant Staphylococcus aureus (USA300) reaches 99.86±0.12%, while the antibacterial effect against Pseudomonas aeruginosa (PA01) reaches 91.97±0.37%. This indicates that the carbon dots prepared by this invention exhibit excellent broad-spectrum antibacterial properties and synergistic antibacterial effects. At the same time, different ratios of silane chains to nitrogen sources can also directionally enhance the killing effect on specific bacterial species, demonstrating a certain degree of selectivity.

[0047] The excellent broad-spectrum antibacterial properties and synergistic antibacterial effects of carbon dots are only reflected in the addition of a specific ratio of nitrogen / silane chains. When this ratio is exceeded, the antibacterial effect will be greatly reduced. For example, the antibacterial results of Comparative Examples 3 and 4 show that when the nitrogen / silane chain addition ratio is 1:1 (Comparative Example 3), the antibacterial effect against methicillin-resistant Staphylococcus aureus (USA300) is 81.25±0.15%, while the antibacterial effect against Pseudomonas aeruginosa (PA01) is 73.45±0.15%. When the nitrogen / silane chain addition ratio was 15:1 (Comparative Example 4), the antibacterial effect against methicillin-resistant Staphylococcus aureus (USA300) was 80.15±0.14%, while the antibacterial effect against Pseudomonas aeruginosa (PA01) was 71.65±0.42%. Both were close to the antibacterial effect of the single modified carbon dots with silane chains (Comparative Example 2), indicating that when the ratio between nitrogen and silane chains exceeds the range, the antibacterial effect will decrease significantly and the synergistic antibacterial effect will not be achieved.

[0048] Test Example 3 The bacterial morphology of the carbon-doped methicillin-resistant Staphylococcus aureus (USA300) and Pseudomonas aeruginosa (PA01) strains from Examples 1-3 was observed by scanning electron microscopy (SEM) 12 h later.

[0049] Logarithmic growth phase bacteria were collected, washed twice with PBS and resuspended to OD=0.5. Different concentrations of carbon dots from various embodiments (MIC concentrations) were added for sterilization for 4 hours. The precipitate was then centrifuged at 5000g for 5 minutes, washed twice with PBS, and resuspended in 2.5% glutaraldehyde fixative (to ensure complete bacterial dispersion, 4°C) overnight in the dark. The precipitate was washed once with PBS and then dehydrated using a gradient of 30%, 50%, 70%, 90%, and 100% ethanol for 10 minutes each time on a shaker at room temperature, centrifuged at 5000 rpm for 8 minutes each time. Finally, the bacteria were dispersed in 200 μL of 100% ethanol and added dropwise onto a silicon wafer (10 μL or 20 μL, depending on the wafer size). After drying, the wafer was sprayed with gold and observed.

[0050] The results are as follows Figure 6 As shown in the figure. The results showed that the untreated bacteria had intact structures, while the bacteria treated with carbon dots all exhibited significant membrane shrinkage and damage, revealing the mechanism by which carbon dots achieve bactericidal effects by disrupting the bacterial membrane structure.

[0051] Test Example 4 The toxicity of the carbon dots from Examples 1-3 at MIC concentrations to RAW 264.7 cells was evaluated using the CCK8 assay. Serial concentrations of the solutions were prepared using sterile PBS. RAW 264.7 cells were seeded in 96-well plates, and the cell density was adjusted to 5 × 10⁶ cells / well.4 Cells were cultured at 37°C for 12 h in a 5% CO2 incubator. Then, 100 μL of carbon dots from Examples 1-3 (final concentrations of 1 mg / mL, 0.5 mg / mL, 0.25 mg / mL, and 0.125 mg / mL) were added to each well. A control group (10% FBSDMEM medium + cells) and a blank group (10% FBS DMEM medium) were also included. After a second co-incubation at 37°C with 5% CO2 for 24 h, 100 μL of 10% CCK8 medium was added to each well for 1 h of incubation. The absorbance was measured at 450 nm using a microplate reader. The cytotoxicity of the drug was evaluated based on the cell viability (CV%). Each group was repeated six times, and the average value was taken.

[0052] Cell viability can be calculated using the following formula:

[0053] Where As is the absorbance of the experimental group, Ab is the absorbance of the blank group, and Ac is the absorbance of the control group.

[0054] The results are as follows Figure 7 As shown, the results indicate that a series of carbon dots had no significant effect on cell viability. When the concentration reached 1 mg / mL, the cell viability remained above 90%, which fully demonstrates that carbon dots have good cell compatibility.

[0055] The applicant declares that the technical solution of this invention is illustrated by the above embodiments, but this invention is not limited to the above embodiments, that is, it does not mean that this invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials for the products of this invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of this invention.

[0056] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0057] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

Claims

1. A nitrogen-doped phenolic acid carbon dot with a surface modified with silane chains, characterized in that, The carbon dot consists of a carbon core and dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride modified on the surface of the carbon core. The carbon core is a carbon skeleton formed by hydrothermal carbonization using gallic acid as a carbon source. The carbon skeleton is doped with nitrogen, and the nitrogen source is ethylenediamine.

2. The method for preparing nitrogen-doped phenolic acid carbon dots with surface-modified silane chains according to claim 1, characterized in that, Includes the following steps: (1) Gallic acid, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and ethylenediamine were dissolved in a mixed solvent consisting of ultrapure water and ethanol to obtain a precursor solution; (2) The precursor solution obtained in step (1) is placed in a reaction vessel for hydrothermal reaction; (3) After the reaction is complete, allow the mixture to cool naturally, centrifuge the product and take the supernatant. (4) The supernatant was placed in a dialysis bag for dialyzing, and after freeze-drying, nitrogen-doped phenolic acid carbon dots with silane chains on the surface were obtained.

3. The method for preparing nitrogen-doped phenolic acid carbon dots with surface-modified silane chains according to claim 2, characterized in that, In step (1), gallic acid: dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride: ethylenediamine = (1-2) g: (2-10) mL: 1 mL.

4. The method for preparing nitrogen-doped phenolic acid carbon dots with surface-modified silane chains according to claim 2, characterized in that, In step (1), the volume ratio of ultrapure water to ethanol in the mixed solvent is 60:40, and the amount used is 30 mL.

5. The method for preparing nitrogen-doped phenolic acid carbon dots with surface-modified silane chains according to claim 2, characterized in that, In step (2), the reactor is heated to 160-220°C at a heating rate of 2-5°C / min and reacted for 12-18 h.

6. The method for preparing nitrogen-doped phenolic acid carbon dots with surface-modified silane chains according to claim 2, characterized in that, In step (3), the centrifugation speed is 8000-12000 r / min and the time is 10-15 min.

7. The method for preparing nitrogen-doped phenolic acid carbon dots with surface-modified silane chains according to claim 2, characterized in that, In step (4), the molecular weight retained by the dialysis bag is 1000-1500 Da.

8. The application of nitrogen-doped phenolic acid carbon dots with surface-modified silane chains as described in claim 1 in the preparation of antibacterial drugs.